Syntheses and applications of phosphine- N- heterocyclic carbene metal complexes via catalytic asymmetric hydrophosphination - Seah, Jeffery Wee Kiong (Nanyang Technological University, 2022)
Chiral hybrid phosphine- N-heterocyclic carbenes form a unique class of bidentate ligands which finds extensive uses as privileged ligands in homogeneous transition metal catalysis. The current methodologies associated with their syntheses suffer from significant drawbacks and the diversity of the structural backbones of these ligands has hence been limited. Catalytic asymmetric hydrophosphination was contrived as a solution to address the abovementioned problem as it is arguably one of the most efficient methods of generating chiral phosphines with high enantiopurities and simultaneously, offering additional advantages such as a 100% atom economy, mild reaction conditions and a diverse substrate scope. Catalytic asymmetric hydrophosphination was employed in the syntheses of novel chiral phosphine- N- heterocyclic carbene precursors and these precursors were subsequently transformed into chiral novel phosphine- N- heterocyclic carbene metal complexes. The structures of the complexes were elucidated via X-ray crystallography and their catalytic and biological applications were explored.